2013
DOI: 10.1007/s10334-013-0387-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo chlorine and sodium MRI of rat brain at 21.1 T

Abstract: Object MR imaging of low-gamma nuclei at the ultrahigh magnetic field of 21.1 T provides a new opportunity for understanding a variety of biological processes. Among these, chlorine and sodium are attracting attention for their involvement in brain function and cancer development. Materials and methods MRI of 35Cl and 23Na were performed and relaxation times were measured in vivo in normal rat (n = 3) and in rat with glioma (n = 3) at 21.1 T. The concentrations of both nuclei were evaluated using the center-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 22 publications
4
65
0
Order By: Relevance
“…For the in vivo relaxation time constants, a direct comparison between the two magnetic fields was not possible, as no dedicated RF coils for small‐animal imaging were available at the 7.0‐T whole‐body MRI system. However, the measured T 1 relaxation times of 23 Na were similar to those obtained previously at 21.1 T . As expected from the phantom experiments, the in vivo 39 K relaxation times are shorter than those of 23 Na.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For the in vivo relaxation time constants, a direct comparison between the two magnetic fields was not possible, as no dedicated RF coils for small‐animal imaging were available at the 7.0‐T whole‐body MRI system. However, the measured T 1 relaxation times of 23 Na were similar to those obtained previously at 21.1 T . As expected from the phantom experiments, the in vivo 39 K relaxation times are shorter than those of 23 Na.…”
Section: Discussionsupporting
confidence: 88%
“…A three‐dimensional back‐projection MRI pulse sequence, as described in ref. , was applied to acquire 23 Na MR and 39 K MR images of the healthy rat brain (Fisher 344 rats, n = 2). The center‐out readout direction was rotated in plane using nv steps of 360°/ nv increments [ nv ( 23 Na MRI) = 80, nv ( 39 K MRI) = 32], and each plane was rotated using nv 1 steps of 180°/ nv 1 increments [ nv 1 ( 23 Na MRI) = 60, nv 1 ( 39 K MRI) = 30] .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, increased sodium in vitreous humor increases excitability of light receptors in the eye and causes photosensitivity [30]. The biological implications of imaging other low gyromagnetic nuclei are just beginning to be studied [31].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…This is partly because of the challenge of measuring tissue ion content in vivo, especially from the intracellular compartment. It has been reported that, using MR imaging with dedicated RF coils and UTE sequences, it is possible to obtain in vivo Na + , K + , and Cl − concentration measurements, despite their much lower MR imaging sensitivity and lower SNR compared to that of hydrogen ( 1 H) . Unfortunately, compared to Na + MR imaging, K + and Cl − mapping are usually performed with an ultra‐high field MRI scanner and dedicated RF coils.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that, using MR imaging with dedicated RF coils and UTE sequences, it is possible to obtain in vivo Na + , K + , and Cl − concentration measurements, despite their much lower MR imaging sensitivity and lower SNR compared to that of hydrogen ( 1 H). [19][20][21][22] Unfortunately, compared to Na + MR imaging, K + and Cl − mapping are usually performed with an ultra-high field MRI scanner and dedicated RF coils. In addition, the spatial resolution is usually large, which may limit the quantification in sub-regions.…”
Section: Introductionmentioning
confidence: 99%